The Review Study of Halal Products and Its Impact on Non-Muslims Purchase Intention - Aransyah, Muhammad Fikry; Furqoniah, Finnah; Abdullah, Amjad Hamad (Universitas Islam Negeri Raden Intan Lampung, 2019)
In a Muslim country, halal products were a norm in the society whereby Muslims in their daily life were not only consuming the halal products. The acceptance of non-Muslims towards halal products is growing as well because of the strict process and laws to follow. It reviews studies and theories on customer’s purchase intention on halal products and the concepts of price, awareness, availability, safety, ingredients, and quality of the halal products, which affect their purpose to buy from the perspective of non-Muslim. Fifty research article from 2009 to 2019 was chosen for this research. Besides, the halal products are also being monitored, certified, and enforced by the government. Halal products with certification will automatically gain the confidant of the consumers without any doubts. There are many types of research being conducted about the halal industry, but there is limited research being conducted to explore the non-Muslim consumers' purchase intention on halal products.Keywords: halal products, purchase intention, non-muslim, literature review